Stabilitas Sabun Cair Wajah yang Mengandung Susu Kambing dengan Variasi Kokamide DEA - TETI INDRAWATI; NELLY WULANDARI (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Goat milk containing many amino acids and fatty acids that can be used as an emollient and humectant in skin liquid soap. The aim of this study is to investigate the effect of variation in cocamide DEA concentration on a face liquid soap stability. Face liquid soap formulae containing 10% goat milk and different concentration of cocamide DEA (3%, 4%, 5%, and 6%) were made by dissolving and mixing methods. The goat milk liquid soap products were evaluated and tested for their stability. Stability were justified from the colour, smell, viscosity, pH, density, and homogenity. The result showed that higher cocamide DEA concentration would produce better soap stability consecutively. The goat milk liquid soap containing 6% of cocamide DEA is the best formula investigated.